Clinical application value of metagenomic next-generation sequencing in the diagnosis of central nervous system infections - Liu, Ying; Zhu, Weiwei; Jiao, Mengfan; Guo, Wenhu; Luo, Yonggang (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Objectives: The purpose of this study is to evaluate the clinical application value of the metagenomic next-generation sequencing (mNGS) in central nervous system (CNS) infections. Methods: Both mNGS and routine examination of cerebrospinal fluid (CSF) samples in patients with CNS infections, retrospective analyzed the efficacy of mNGS on this cohort and ultimately compared with clinical diagnosis. Results: 94 cases consistent with CNS infection were included in the analysis. The positive rate for mNGS is 60.6% (57/94), significantly higher than the traditional detected 20.2% (19/94，P<0.01).mNGS detected 21 pathogenic strains that could not be detected by routine testing. Routine tests were positive for 2 pathogens, but negative for mNGS. The sensitivity and specificity of mNGS in the diagnosis of central nervous system infection were 89.5% and 44%, respectively, compared with traditional tests. The accuracy of mNGS in diagnosing central nervous system infection was 55.3%. At discharge,20(21.3%) patients were cured, 55 (58.5%) patients had improved, 5(5.3%) patients had not recovered, and 2(2.1%) patients died. Conclusions: mNGS has unique advantages in the diagnosis of infection in the central nervous system. mNGS tests can be performed when patients are clinically suspected to have a central nervous system infection but have no pathogenic evidence.